Perencanaan Ruang Terbuka Publik di Natas Lehong, Kabupaten Manggarai Timur sebagai Tempat Rekreasi - Jostar Jovandri Noari Parera; I Made Sukewijaya (Nandur, 2024)
Natas Lehong is one of the public open spaces in East Manggarai Regency which has an area of 2,86 Ha. Natas Lehong is a public open space that has a main function as a ceremonial field. In addition to its main function, Natas Lehong has another supporting function as a recreational facility. However, the supporting function cannot run well due to the lack of facilities that support recreational activities such as jogging tracks, park benches, playground areas, food and beverage stalls, and other supporting facilities. This research aims to plan public open space in Natas Lehong, Borong City, East Manggarai Regency as a place for recreation. This research uses a survey method with descriptive analysis and uses a qualitative research approach. The basic concept of this research is "Natas beo". Natas beo in the culture of the Manggarai people means, a village courtyard that functions as a public space for the community, such as traditional ceremonial activities, cultural performance activities, sports activities, playing for children and families. The final result of this research is a public open space planning in Natas Lehong which is divided into three spaces, namely public zone, semi-public zone, service zone. This research discusses the planning of public open space as a recreation area, so further research is needed to further examine the design and application of Natas Lehong.